Promoting coalescence of droplets in oil subjected to pulsed electric fields: changing and matching optimal electric field intensity and frequency for demulsification. Issue 9 (2nd September 2019) - Gong, Haifeng; Yu, Bao; Peng, Ye; Dai, Fei
Abstract: Droplets in oil undergo stretching deformation and vibration under a pulsed electric field. This process is very effective in promoting the coalescence of droplets and separating water from oil. However, the electric field parameters for optimal coalescence vary with the change of the particle size of droplets during coalescence. To respond to the changes in the radii of droplets, the optimal electric field intensity and frequency should be switched and adjusted for efficient demulsification. In this study, the influence of the dynamic change of the electric field intensity and frequency on coalescence of droplets was investigated by experimental methods. The electric field parameters were determined by a mapping method. And the switching time interval of electric field for efficient coalescence was obtained by utilizing a model of coalescence of double droplets. The experimental results show that the coalescence of droplets in a variable pulsed electric field, with changing intensity and frequency (<1000 Hz) in certain switching time, is better than in a constant pulsed electric field. And the efficient demulsification frequency and intensity tend to decrease with increasing droplets size. In addition, the viscosity and relative permittivity of oil have a significant influence on the electric field frequency and intensity for efficient demulsification. Graphical Abstract: